Implementasi Model Teams Games Tournament terhadap Memberikan Motivasi Belajar Peserta Didik Pembelajaran Sejarah Kebudayaan Islam - Imron Julianto; Surya Hadi Dharma; H.TB.Abdul Hamid (CV Putra Publisher, 2024)
Many Class X students feel bored when studying SKI, because SKI teachers still use the lecture method, not the Teams Games Tournament model. Students have not been motivated by SKI teachers. The SKI score assessment is still low, namely an average of 6. The aim of the research is to find out how SKI teachers plan their teaching and how to apply/implement the Teams Games Tournament model to provide student learning motivation in learning the History of Islamic Culture and how SKI teachers motivate student learning in class X. This research method uses a qualitative method with the PTK research type. The data sources in this research are primary class X students and SKI teachers. Secondary sources; relevant books, journals, websites. The research results show that the planning for implementing SKI learning is good, and the implementation of SKI lessons is carried out well using the Teams Games Tournament model. Students become active and creative and also motivated to learn SKI. The result is that the SKI value increases, the initial value of 6 can increase to 7. The initial value of 7 increases to 8 and the initial value of 8 increases to 9.